2013
DOI: 10.1002/alr.21156
|View full text |Cite
|
Sign up to set email alerts
|

Safety and outcomes following hybrid balloon and balloon‐only procedures using a multifunction, multisinus balloon dilation tool

Abstract: These results indicate that a multifunctional, malleable, balloon-dilating device can be safely and successfully used to treat multiple sinuses with sustained ostial patency and symptom improvement for at least 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
1
25
0
2
Order By: Relevance
“…26 In this study, the number of reported rhinosinusitis episodes per patient requiring medication in the year before intervention was between four and five, which is similar to the general population of patients undergoing FESS or balloon dilation who report between three and four episodes in the year leading up to treatment. 8,16,17,27,28 The large number of pretreatment rhinosinusitis episodes is not surprising because our study population met specific criteria before enrollment that included failure to improve despite multiple rounds of medical therapy. The significant reduction in the number of rhinosinusitis episodes requiring antibiotics in our study is consistent with other standalone balloon dilation studies and further shows the clinical usefulness and potential cost-savings of balloon dilation.…”
Section: Discussionmentioning
confidence: 99%
“…26 In this study, the number of reported rhinosinusitis episodes per patient requiring medication in the year before intervention was between four and five, which is similar to the general population of patients undergoing FESS or balloon dilation who report between three and four episodes in the year leading up to treatment. 8,16,17,27,28 The large number of pretreatment rhinosinusitis episodes is not surprising because our study population met specific criteria before enrollment that included failure to improve despite multiple rounds of medical therapy. The significant reduction in the number of rhinosinusitis episodes requiring antibiotics in our study is consistent with other standalone balloon dilation studies and further shows the clinical usefulness and potential cost-savings of balloon dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Sie stellt eine der in den letzten Jahren am intensivsten diskutierte Innovation in der Nasennebenhöhlenchirurgie dar -nicht nur, weil diese Methode intensiv durch eine breit angelegte Mediendarstellung veröffentlicht wurde und hierbei hohe Erwartungen bei Patienten erwuchsen [1068][1069][1070][1071], sondern auch, weil bis heute der eigentliche Benefit der Ballondilatation bei der Therapie sinunasaler Erkrankung nicht ausreichend geklärt ist, trotz der Vielzahl vorliegender Publikationen [1067,1073,1074]. Zentrale Probleme in der Bewertung der Ballondilatation betreffen u. a. die Methodik der Studien: nicht eindeutig benannte und definierte Indikation [1065,[1075][1076][1077][1078][1079], retrospektive Studien [1070,1076,[1080][1081][1082], Mischung verschiedener Krankheitsbilder [627,855,1070,1078,[1083][1084][1085], Mischung alleiniger Ballondilatation mit Hybrid-Eingriffen oder anderen Therapien [854,855,1065,1075,1076,1078,1080,1083,[1085][1086][1087][1088]. Gelegentliche kritische Kommentare betrafen die Methodik veröffentlichter Arbeiten zur Ballondilatation [1089,1090].…”
Section: Ballondilatationunclassified
“…Eine Vielzahl von Fallserien, retro-und prospektiven Studien mit sehr unterschiedlichen Patienten gibt insgesamt und durchgehend hohe Erfolgsraten an [1065, 1075-1078, 1084, 1107]: ▶ Eine Dilatation der einzelnen Nasennebenhöhlen ist teilweise in weit über 90 % möglich ▶ Die Zugänge bleiben in 80 bis > 90 % nach endoskopischem und CT-Befund offen ▶ Eine Symptomverbesserung wird in 85-95 % angegeben, die auch über 2 Jahre weitgehend persistiert ▶ Die Lebensqualität nimmt postoperativ signifikant zu ▶ Die Häufigkeit akuter Infektionen, der Medikamentenverbrauch und Fehlzeiten am Arbeitsplatz sinken ▶ Die Revisionsrate beträgt kurzfristig 1-2 % und nimmt innerhalb von 2 Jahren auf bis 9 % zu (auf Patienten bezogen; [1077]). ▶ Technische Fehlfunktionen treten in 1,7-3,4 % auf [1065,1078]. Ähnlich gute Ergebnisse werden von der transantralen BD der Kieferhöhle und des Infundibulum ethmoidale bei umschriebener therapierefraktärer chronischer Sinusitis der Kieferhöhle und ggf.…”
Section: Ballondilatationunclassified
“…There, nonetheless, is an expanding role for less-invasive surgical procedures that are being used in pediatric as well as adult patients with CRS, such as the use of balloon sinus ostial dilatation 73 and hybrid procedures (e.g., limited FESS plus balloon sinus ostial dilatation). 74 The main arguments against the use of FESS in children are (1) the relatively high success rate of more conservative medical or surgical approaches, and (2) concern about the overuse of endoscopic surgery. 75 However, early concerns that pediatric FESS would have adverse long-term consequences, such as detrimental effects on facial development, have proven to be unfounded.…”
Section: The Role For Functional Endoscopic Sinus Surgery and More Comentioning
confidence: 99%